Wellbeing of School Communities in the Context of COVID-19 Pandemic: A Qualitative Study in Chilean Low-SES Schools - López, Verónica; Ramírez, Lorena; López-Concha, Romina; Ascorra, Paula; Álvarez, Juan Pablo; Carrasco-Aguilar, Claudia; Jervis, Pamela; Squicciarini, Ana María; Simonsohn, Ariela; Contreras, Tabata; Opazo, Héctor (Frontiers in Psychology, 2022)
The COVID-19 pandemic continues to impact schools and how education is conveyed to students. One of the aspects that has gained strength is supporting the wellbeing of educational communities. The purpose of this study was to describe and understand the construction of school wellbeing during the pandemic, based on the notion of collective and sustainable wellbeing. Through a qualitative design, we conducted a study in four Chilean low-SES schools in which a national school mental health program is implemented. A total of 41 in-depth interviews and one group interview were conducted with students, parents, teacher, teacher assistants, school principals, psychosocial professionals, and the school mental health officers during the second half of the 2020 school year. Thematic content analyses showed that, while facing the school closure challenges, schools strived to protect students’ and teachers’ wellbeing. However, participants highlighted necessary conditions for sustaining the school community’s wellbeing and mental health in the context of the COVID-19 pandemic: assuring digital connectivity for all students; coordinated work with families and within the school; strengthening networks; curriculum adaptation and diversified pedagogical strategies; and emotional support toward teachers, families, and students. We discuss these findings and their implications for a sustainable and collective perspective of the wellbeing of school communities in low-SES schools, as well as for policy, practice, and research from the perspective of schools for social justice and health promotion.